2020
DOI: 10.1111/are.14502
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition of wild and cultured seahorses (Hippocampus kudaBleeker)

Abstract: The seahorse has been used for thousands of years as an important traditional Chinese medicine (TCM) in China. Many species of wild seahorse have become endangered, but demand for them continues to grow rapidly. Therefore, it is urgent to cultivate seahorses to relieve the strain on natural populations and meet the market demand for this TCM. In this study, medicinal components of wild and cultured yellow seahorses (Hippocampus kuda Bleeker) were analysed and compared. Different parts of the body (cortex and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…Lin et al (2008) found that the total amount of amino acids was as high as 50-60% (based on a comparison of their retention times with those of amino acid standards) in six species of Hippocampus, and eight types of essential amino acids accounted for 17-20% of the total amino acid content, which indicated that the Hippocampus is a high-quality protein source. The content of glycine was the highest (83.98 mg/g) among the 15 types of amino acids in Hippocampus kuda Bleeker and Hippocampus trimaculatus Leach (Sun et al, 2020). In addition, Hippocampus is also rich in glutamic acid, aspartic acid, alanine, and arginine (Lin et al, 2009).…”
Section: Amino Acids and Peptidesmentioning
confidence: 95%
See 4 more Smart Citations
“…Lin et al (2008) found that the total amount of amino acids was as high as 50-60% (based on a comparison of their retention times with those of amino acid standards) in six species of Hippocampus, and eight types of essential amino acids accounted for 17-20% of the total amino acid content, which indicated that the Hippocampus is a high-quality protein source. The content of glycine was the highest (83.98 mg/g) among the 15 types of amino acids in Hippocampus kuda Bleeker and Hippocampus trimaculatus Leach (Sun et al, 2020). In addition, Hippocampus is also rich in glutamic acid, aspartic acid, alanine, and arginine (Lin et al, 2009).…”
Section: Amino Acids and Peptidesmentioning
confidence: 95%
“…The contents of essential amino acids and unsaturated fatty acids were much higher in cultured Hippocampus kuda Bleeker than in wild Hippocampus. In terms of mineral elements, Se, Fe, Cu, and Ca were much more abundant in wild Hippocampus (Sun et al, 2020). Lin et al (2009) showed that the contents of DHA and EPA in cultured Hippocampus trimaculatus Leach were nearly two times as high as those in wild Hippocampus, and the proportions of polyunsaturated fatty acids in total fatty acids were 31.89 and 21.39%, respectively.…”
Section: Wild Types and Cultured Typesmentioning
confidence: 97%
See 3 more Smart Citations